2014
DOI: 10.1038/nature13706
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 ensures intestinal homeostasis by protecting the epithelium against apoptosis

Abstract: Receptor interacting protein kinase 1 (RIPK1) has an essential role in the signalling triggered by death receptors and pattern recognition receptors. RIPK1 is believed to function as a node driving NF-κB-mediated cell survival and inflammation as well as caspase-8 (CASP8)-dependent apoptotic or RIPK3/MLKL-dependent necroptotic cell death. The physiological relevance of this dual function has remained elusive because of the perinatal death of RIPK1 full knockout mice. To circumvent this problem, we generated RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
269
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(279 citation statements)
references
References 42 publications
8
269
2
Order By: Relevance
“…Although access to detailed histopathological analysis was not available to us in this study, it is notable that the DKO phenotype bears similarity to that reported recently for selective RIPK1 KO in intestinal epithelial cells. [50][51][52] The latter involves kinaseindependent RIPK1 activity, which confers stabilization of several pro-survival proteins, including TRAF2, cIAPs and cFLIP. 52 It will be interesting to investigate whether TRAF2 is linked to the kinase-independent functions of RIPK1 and/or RIPK3.…”
Section: Discussionmentioning
confidence: 99%
“…Although access to detailed histopathological analysis was not available to us in this study, it is notable that the DKO phenotype bears similarity to that reported recently for selective RIPK1 KO in intestinal epithelial cells. [50][51][52] The latter involves kinaseindependent RIPK1 activity, which confers stabilization of several pro-survival proteins, including TRAF2, cIAPs and cFLIP. 52 It will be interesting to investigate whether TRAF2 is linked to the kinase-independent functions of RIPK1 and/or RIPK3.…”
Section: Discussionmentioning
confidence: 99%
“…RIP1 functions to protect cells from excessive caspase-8-mediated apoptosis and TNF-driven inflammation to maintain cell homeostasis in barrier tissues such as the gut epithelium and skin. 28,29 Pyroptosis. Cell death by pyroptosis was first observed in macrophages following infection with Shigella flexneri or Salmonella typhimurium.…”
Section: Caspases In Non-apoptotic Cell Deathmentioning
confidence: 99%
“…40 Recently, in a mouse model of inflammation in the skin that is induced by SHARPIN-deficiency, RIPK1 kinase-dead mice displayed significant rescue, 20 whereas in the models of gut inflammation the kinase activity of RIPK1 did not promote severe colitis. 24,41 Further, it was shown that RIPK1 and RIPK3 are found in a complex with caspase 8 and caspase 1 where the kinase activity of RIPK1 is dispensable. 42,43 However, in vivo deficiency of RIPK1 kinase activity is shown to be deleterious for the host after Vaccinia virus infection.…”
Section: Ripk1 Interacts With Various Proteins Such As Ciaps Andmentioning
confidence: 99%